“BETTER AIRPORTS” PACKAGE: EU LEGISLATIVE TREND IN THE AIRPORT SECTOR - Arber Gjeta (European Scientific Journal, ESJ, 2015)
Through this paper we aim to illustrate the latest proposals within EU legislation regarding airports, which are facing some difficulties in the EU legislative iter of approval. Airports, due to the liberalization and deregulation process, shifted from an appendix facility of air transport into a self-standing industry. The whole process was imprinted by the massive privatization and is leading now into a competitive and common market, at least in EU level. These proposals, regarding slot allocation, groundhandling and procedure for restriction of the noise related operations, are to be considered as a serious effort for a comprehensive regulation. In our view, de lege ferenda it is a welcome initiative which yet represents difficulties in reaching uniformity within Union airport market. Furthermore, it is time for the Commission to launch new package related to the State Aids in the Air Transport sector and specifically, those which deals with airports.